An invitation to fly : basics for the private pilot - Glaeser, Dennis; Gum, Sanford; Walters, Bruce (Bruce E.); Gum, Sanford (Belmont, Calif. : Wadsworth Pub. Co., 1985)
"An Invitation to Fly : Basics for the private pilots is designed to help you, the potential private pilot, to become a safe and competent pilot and to successful complete the ground portion of your training." It is designed to be used in ground schools that are approved under part 141 of the Federal Aviation Regulations. It is, of course, also suitable for those individuals who seek a Private Pilot Certificate under FAR part 61 and who are not affiliated with an approved school."
Updated ed. of: An invitation to fly / Sanford Gum & Bruce Walters. c1982.
Includes indexes.
English text.
Keywords: Private flying